Análise da morbidade hospitalar por doenças crônicas não transmissíveis e o itinerário terapêutico dos idosos no cuidado das doenças isquêmicas do coração - Biulchi, Ciana Minuzzi Gaike (2014)
Technological advances, accomplishments in the field of health sciences, changes and improvement in life and work routines are factors that contributed to population longevity. A dynamic epidemiological change emerged along with demographic transition, altering the prevalence and incidence of Chronic Non-Communicable Diseases, and interfering in life and health conditions of Brazilians. The study aimed to analyze the health situation of elderly people with Chronic Non-Communicable Diseases; residents of the State of Rio Grande do Sul, Brazil, from the analysis of hospital morbidity by chronic non-communicable diseases, in the period of 2001 to 2010, and from the therapeutic itinerary. By encouraging the discussion about the State s health situation and the development of modifying actions and incentives of the health administration process, it was sought to contribute to health planning in demands regarding Chronic Non-Communicable Diseases, and to provide aid for the creation of public policies capable of attending users needs for care. This dissertation is presented in the form of two articles. The first article discusses the analysis of hospital morbidity in the state of Rio Grande do Sul, Brazil, from 2001 to 2010, providing an outlook of admissions of elderly people aged 60 years or older, through an ecological study using data available in the Hospital Information System of the Department of Informatics of the Unified Health System, and powered by the authorization for hospital admission. The aim of this study was the three main causes of admission by Chronic Non-Communicable Diseases in the elderly for the referred period: diseases of the circulatory, respiratory systems, and neoplasia. The second article is about a qualitative study on the therapeutic itinerary of elderly people from Passo Fundo/RS, Brazil with ischemic heart diseases, and it sought to unfold the path created by these elderly people in the search for care. After analyzing hospital morbidity by Chronic Non-Communicable Diseases in elderly people from the State of Rio Grande do Sul, and after knowing the therapeutic itinerary of elderly people with ischemic heart diseases, residents of Passo Fundo/RS, it may be inferred that the relation between data gathered in information systems of the Ministry of Health, and the approach by listening to the needs of users may properly supply the planning of health actions. Thus, professionals, administrators, and the community should be willing to refine their perception on the epidemiological situation presented, paying attention to the numbers as well as perceiving possible flaws in health services in the speech and attitudes of the user. This work indicates some intersections that should still be detailed, and it opens room for other questions that will add to information here presented always with the intention of contributing to scientific knowledge, reflecting as benefits to society